Fixed features of future networks based on future applications - Yawen ZHANG; Miao WANG; Linghao WANG; Hanwen ZHANG; Yujun ZHANG (Dianxin kexue)
More and more network applications place higher demands on the network functions and performance.Internet of vehicles requires the network to support low latency and high reliability,telemedicine requires it with deterministic latency and security assurance,the industrial internet requires networks to meet large connections and high reliability,AR/VR applications require low latency and high bandwidth,quantum computing also brings new challenges to network security.Due to the limitations of its own architecture,existing IP networks only provide best-effort services that cannot meet the needs of future network applications.Future network applications in the next 20 years were investigated,the functional and performance of the future network were analyzed.By describing the application scenarios of internet of vehicles,telemedicine,industrial internet AR/VR and quantum computing,the network performance to meet the needs of these scenarios was analyzed and the performance indicators of future networks were obtained.